2022
DOI: 10.1111/dom.14714
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MiniMed 780G system performance in users aged younger and older than 15 years: Evidence from 12 870 real‐world users

Abstract: Aim To investigate real‐world glycaemic outcomes and goals achieved by users of the MiniMed 780G advanced hybrid closed loop (AHCL) system aged younger and older than 15 years with type 1 diabetes (T1D). Materials and Methods Data uploaded by MiniMed 780G system users from 27 August 2020 to 22 July 2021 were aggregated and retrospectively analysed based on self‐reported age (≤15 years and >15 years) for three cohorts: (a) post‐AHCL initiation, (b) 6‐month longitudinal post‐AHCL initiation and (c) pre‐ versus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
73
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 39 publications
6
73
1
Order By: Relevance
“…Data obtained from 12 870 users of the MiniMed 780G system are consistent with previous real-world analyses, 1 smaller cohorts and clinical studies 4,15,16 and thus provide further evidence relating to the robust nature of the outcomes achieved with the 780G system. The robustness of the results across different countries and age groups (reported by Arrieta et al 17 ), combined with the sustained results beyond the initial interest in a new device, attest to the nature of the therapy, which is less dependent on users and their health care professionals (HCPs) and relies more on device automation. The decreasing role of users and HCPs, in terms of glycaemic control, is not trivial and was apparent from the first steps of automation, when insulin suspension before low glucose algorithms were adopted to minimize hypoglycaemia.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Data obtained from 12 870 users of the MiniMed 780G system are consistent with previous real-world analyses, 1 smaller cohorts and clinical studies 4,15,16 and thus provide further evidence relating to the robust nature of the outcomes achieved with the 780G system. The robustness of the results across different countries and age groups (reported by Arrieta et al 17 ), combined with the sustained results beyond the initial interest in a new device, attest to the nature of the therapy, which is less dependent on users and their health care professionals (HCPs) and relies more on device automation. The decreasing role of users and HCPs, in terms of glycaemic control, is not trivial and was apparent from the first steps of automation, when insulin suspension before low glucose algorithms were adopted to minimize hypoglycaemia.…”
Section: Discussionmentioning
confidence: 80%
“…In screening variables for statistical associations with higher TIR, several demographic factors were noted as important; increase in age was associated with a 2.5 percentage points increase in TIR for users aged >55 years versus those aged ≤15 years, and male users had on average 0.9% higher TIR relative to female users. Although the changes were statistically significant, the overall outcomes across all ages and genders were well within the recommended guidelines 8 and the traditional gap in control in the younger versus older population 11,19 is diminished with the AHCL system 17 . The use of technology in older age groups has been associated with good glycaemic control 20‐22 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We describe stable BMI z-scores of children and adolescents with T1D using the AHCL system during a 1-year follow up which is the first such long observation (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Similar results, also for a pediatric cohort of individuals with T1D, were obtained by Tornese et al, who reported no change in BMI zscore after 6 months of insulin treatment using either the hybrid closed-loop (Minimed 670G) or AHCL (Minimed 780G) systems.…”
Section: Discussionmentioning
confidence: 99%